Towards automated coronary artery segmentation: A systematic review. (October 2022) - Gharleghi, Ramtin; Chen, Nanway; Sowmya, Arcot; Beier, Susann
Highlights: Methods for segmenting coronary arteries are systematically reviewed. Segmentation of the arteries are vital in both research and clinical applications. Current trends and state of the art segmentation algorithms are explored. Abstract: Background and Objective: Vessel segmentation is the first processing stage of 3D medical images for both clinical and research use. Current segmentation methods are tedious and time consuming, requiring significant manual correction and hence are infeasible to use in large data sets. Methods: Here, we review and analyse available coronary artery segmentation methods, focusing on fully automated methods capable of handling the rapidly growing medical images available. All manuscripts published since 2010 are systematically reviewed, categorised into different groups based on the approach taken, and characteristics of the different approaches as well as trends over the past decade are explored. Results: The manuscripts were divided intro three broad categories, consisting of region growing, voxelwise prediction and partitioning approaches. The most common approach overall was region growing, particularly using active contour models, however these have had a sharp fall in popularity in recent years with convolutional neural networks becoming significantly more popular. Conclusions: The systematic review of current coronary artery segmentation methods shows interesting trends, with rising popularity of machine learning methods, a focus on efficient methods, and falling popularity of computationally expensive processing steps such as vesselness and multiplanar reformation.